COMPARATIVE GROWTH PROMOTING EFFICACY OF FETAL CALF SERUM (FCS) FOR BABY BAMSTER KIDNEY-21 (BHK-21) CELL LINE - S. Rahman; A. Ahmad; S. Bhatti (Journal of Animal and Plant Sciences, 2006)
A study was conducted to evaluate the growth promoting effect of FCS and its proper dilution in cell culture media for persistent cultivation and maintenance of BHK-21 cell culture, by comparing it with other animal sera. Different animal sera of different species as cattle calf serum , Allanto-amniotic fluid , Sheep serum , Poultry serum and Goat serum @ 10% were added to cell culture medium (M 199, Biomedicals; USA). A fast and reliable technique, MTT (3 {4, 5-Dimethyzol-2-Yl} 2, 5-Diphenyl Tetrazolium Bromide) Assay was employed to measure the cell densities in small amount of cell culture media by measuring OD values under 570nm, with 630nm as a reference read out. It was concluded that FCS is the best growth promoting agent for BHK-21 cell line and 5-7.5 % concentration has the desired effect of persistent cultivation and maintenance of BHK-21 cell line.
Keywords: BHK-21 cells; fetal calf serum; cell density; growth promoting factor